2022
DOI: 10.18295/squmj.1.2022.003
|View full text |Cite
|
Sign up to set email alerts
|

Female Genital Tuberculosis Among Infertile Women and Its Contributions to Primary and Secondary Infertility

Abstract: Female genital tuberculosis (FGTB) is an infectious widespread disease among young women. This meta-analysis study aimed to investigate the prevalence of Female Genital Tuberculosis among infertile women and its contribution to primary and secondary infertility. A PubMed, MEDLINE, world cat log, Lens.org, direct Google search, Google Scholar, and Researchgate, from 1971 to July 17, 2021, were searched using the keywords; prevalence, epidemiology, urogenital tuberculosis, FGTB, infertile women, infertility comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Female GT is a significant contributor to morbidity and infertility, particularly in regions with a high incidence of tuberculosis [ 4 ]. Most patients suffer from this disease asymptomatically or with clinically insignificant symptoms, which are diagnosed after evaluation for infertility, which affects between 60 and 80 % of women suffering from the disease [ 3 , 4 ]. In view of this problem, scientometrics allows the analysis of scientific production and its development as an information process, using quantitative methods, with the purpose of knowing the impact and characteristics of research for making strategic decisions for research funding and facilitating collaboration among researchers [ [10] , [11] , [12] ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Female GT is a significant contributor to morbidity and infertility, particularly in regions with a high incidence of tuberculosis [ 4 ]. Most patients suffer from this disease asymptomatically or with clinically insignificant symptoms, which are diagnosed after evaluation for infertility, which affects between 60 and 80 % of women suffering from the disease [ 3 , 4 ]. In view of this problem, scientometrics allows the analysis of scientific production and its development as an information process, using quantitative methods, with the purpose of knowing the impact and characteristics of research for making strategic decisions for research funding and facilitating collaboration among researchers [ [10] , [11] , [12] ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis comprising 42 studies revealed that, of the 30,918 women surveyed, roughly 20 % experienced infertility. This was predominantly observed in countries with limited resources [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hospital Universitário Getúlio Vargas da Universidade Federal do Amazonas (HUGV-UFAM), Manaus -AM 2. Faculdade de Medicina da Universidade Federal do Amazonas (FM-UFAM), Manaus -AM 3.…”
unclassified